Susut Tegangan pada Penghantar ACCC di Saluran Transmisi 150 kV di PT. PLN (Persero) Unit Pelayanan Transmisi Pekanbaru: Transmisi - Octary, Wellington; Eteruddin, Hamzah; Tanjung, Abrar (Teknik Elektro Universitas Lancang Kuning, 2020)
Power transmission network system plays an important role in distributing power, especially in 150 kV power transmission lines. In 2013, the was a change in term of conductor type in in 150 kV transmission lines of Garuda Sakti – Balai Pungut, from ACSR to ACCC, because of the growing number of power plants in Riau and power distribution in every conductor supplying higher current, when given higher current, ACCC conductor is capable of transmitting power twice the ACSR conductor. The single line diagram of UPT Pekanbaru, data from power station (GI) Garuda Sakti – Balai Pungut, conductor data and load data are all data necessary for the study and calculation on ACCC conductor. The result shows that the amount of voltage drop power losses of ACCC conductor is 5.098 kV, while the power loss is 479,187 with the sagging value is 6.950 m, compared to the old conductor, the ACSR type, with the voltage drop of 7.517 kV, power loss of 828.863 kW, and the sagging value of 9.010 m, all measured in 150 kV power transmission lines of PT. PLN PERSERO UPT Pekanbaru.